EXPLORING THE EMERGENCE OF ONLINE GAMES AND THE IMPACT TO OTHER CONVENTIONAL GAMING PLATFORMS IN MANADO - Engka, Nathaneel H.J.; Tulung, Joy E.; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2021)
In this era of technology, Online Game is getting famous because gaming are hobbies for people. Exploring the emergence of Online Games and the impact to the other gaming platform, why they want to play online games rather than the other conventional gaming and could give information to marketer, developer, and publisher in order to improving their business. ThisÂ In this era of technology, Online Game is getting famous because gaming are hobbies for people. Exploring the emergence of Online Games and the impact to the other gaming platform, why they want to play online games rather than the other conventional gaming and could give information to marketer, developer, and publisher in order to improving their business. This research was conducted to identify the immersion attributes for Gamer in Manado City. This research gathered data from 100 respondents, which were taken by using Purposive Sampling method. Correspondence analysis is applied in this research to analyze the immersion attribute and to measure the inertia; in this research the inertia value is 0.152 which is the row-column association is considered significant. Five immersion attributes were found as the important factors in this research. Those attributes are Accessibility, Price, Enjoyment, Social Interaction and Achievement. From the result of data analysis processed by Statistical Product and Service Solution (SPSS) Version 24, Correspondence measurement indicates that the immersion attribute have strong correlation between conventional gaming platforms and immersion attribute using perceptual map. Based on the results of Correspondence Analysis, Accessibility is closely associated with PC game, Price with Mobile Game, Enjoyment with PC game, social interaction with Mobile Game, and Achievement with Console game.Â Keywords: accessibility, price, enjoyment, social interaction, achievement, mobile gaming